IW Monetary Outlook: ECB at the Crossroads - Markus Demary; Michael Hüther (Institut der deutschen Wirtschaft (IW), 2017)
The ECB has left its policy interest rates unchanged despite inflationary pressures stemming from a strengthened recovery and from rising oil prices. Although the ECB's Governing Council did not discuss a renewal of the long-term refinancing operations, which will expire in 2020, its monetary policy stance is still too accommodative.
Keywords: 330